Welcome to motherhood - Maruyama, Michiko (Canadian Medical Education Journal, 2019)
My doctors said it was impossible... After all the radiation and chemotherapy, I was told that I would not be able to have children. We searched for a surrogate, we looked into adoption… it seemed so hopeless and then, it happened. I was a bit nervous to tell my program because I am the first University of Alberta cardiac surgery resident to become pregnant. I did not expect their response, “Michiko, our job is to create excellent surgeons. Being an excellent surgeon does not just include being technically skilled. It involves being well rounded and excelling at all areas of life. If part of your life involves being a mother and having a family, then we are here to support and encourage you all the way.” I am proud to share that I am the mother of a beautiful baby boy. "Welcome to Motherhood” is an illustrative photograph that represents my experience as a surgical resident and, at the time, a soon to be mother. I am the first cardiac surgery resident at the University of Alberta to become pregnant. I am so thankful to my program for all their support and encouragement throughout my pregnancy and after, when I entered motherhood. The relevance to cardiovascular science is that I feel it is important to acknowledge my cardiac surgery programs response to my pregnancy announcement. In a male dominated field with no experience of pregnant trainees, they did an incredible job to support and encourage me along the way.